Soil and foliar selenium application: Impact on accumulation, speciation, and bioaccessibility of selenium in wheat (Triticum aestivum L.) - Wang, Min; Zhou, Fei; Cheng, Nan; Chen, Ping; Ma, Yuanzhe; Zhai, Hui; Qi, Mingxing; Liu, Nana; Liu, Yang; Meng, Li; Bañuelos, Gary S.; Liang, Dongli (Frontiers in Plant Science, 2022)
A comprehensive study in selenium (Se) biofortification of staple food is vital for the prevention of Se-deficiency-related diseases in human beings. Thus, the roles of exogenous Se species, application methods and rates, and wheat growth stages were investigated on Se accumulation in different parts of wheat plant, and on Se speciation and bioaccessibility in whole wheat and white all-purpose flours. Soil Se application at 2 mg kg-1 increased grains yield by 6% compared to control (no Se), while no significant effects on yield were observed with foliar Se treatments. Foliar and soil Se application of either selenate or selenite significantly increased the Se content in different parts of wheat, while selenate had higher bioavailability than selenite in the soil. Regardless of Se application methods, the Se content of the first node was always higher than the first internode. Selenomethionine (SeMet) (87%-96%) and selenocystine (SeCys2) (4%-13%) were the main Se species identified in grains of wheat. The percentage of SeMet increased by 6% in soil with applied selenite and selenate treatments at 0.5 mg kg-1 and decreased by 12% compared with soil applied selenite and selenate at 2 mg kg-1, respectively. In addition, flour processing resulted in losses of Se; the losses were 12%-68% in white all-purpose flour compared with whole wheat flour. The Se bioaccessibility in whole wheat and white all-purpose flours for all Se treatments ranged from 6%-38%. In summary, foliar application of 5 mg L-1 Se(IV) produced wheat grains that when grounds into whole wheat flour, was the most efficient strategy in producing Se-biofortified wheat. This study provides an important reference for the future development of high-quality and efficient Se-enriched wheat and wheat flour processing.